Echocardiographic Abnormalities as Independent Prognostic Factors of In-Hospital Mortality among COVID-19 Patients - Pishgahi, Mehdi; Karimi Toudeshki, Kimia; Safari, Saeed; Yousefifard, Mahmoud (Archives of Academic Emergency Medicine, 2021)
Introduction: Direct and indirect sequels of COVID-19 in the cardiovascular system are unclear. The present study aims to investigate the echocardiography findings in COVID-19 patients and possible correlations between the findings and the disease outcome. Methods: In this cross-sectional study, baseline characteristics and echocardiographic findings of hospitalized COVID-19 cases, and their correlation with mortality were evaluated. Furthermore, computed tomography (CT) angiography was performed to assess possible pulmonary embolism. In-hospital mortality was considered as the main outcome of the present study. Results: 680 confirmed COVID-19 cases with the mean age of 55.15 ± 10.92 (range: 28 – 79) years were studied (63.09% male). Analysis showed that history of ischemic heart disease (RR=1.14; 95% CI: 1.08-1.19), history of hypertension (RR=1.04; 95% CI: 1.00-1.08), presence of embolism in main pulmonary artery (RR=1.53; 95% CI: 1.35-1.74), CT involvement more than 70% (RR=1.08; 95% CI: 1.1.01-1.16), left ventricular ejection fraction < 30 (RR=1.19; 95% CI: 1.07-1.32), pleural effusion (RR=1.08; 95% CI: 1.00-1.16), pulmonary artery systolic blood pressure 35 to 50 mmHg (RR=1.11; 95% CI: 1.03-1.18), right ventricular dysfunction (RR=1.54; 95% CI: 1.40-1.08), and collapsed inferior vena-cava (RR=1.05; 95% CI: 1.01-1.08) were independent prognostic factors of in-hospital mortality. Conclusion: Our study showed that cardiac involvement is a prevalent complication in COVID-19 patients. Echocardiography findings have independent prognostic value for prediction of in-hospital mortality. Since echocardiography is an easy and accessible method, echocardiography monitoring of COVID-19 patients can be used as a screening tool for identification of high-risk patients.